2000
DOI: 10.1007/s11325-000-0155-1
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Base Reduction with Radiofrequency Tissue Ablation: Preliminary Results after Two Treatment Sessions

Abstract: Over the last few years, different surgical techniques for the treatment of obstructive sleep apnea syndrome have been developed. While new methods for the treatment of velopharyngeal obstruction turned out to be safe and effective, treatment of hypopharyngeal obstruction due to tongue base hypertrophy has remained, in many aspects, an unsolved problem. Surgical techniques for partial resection of the tongue base (midline glossectomy, lingualplasty) are effective but very invasive procedures requiring temporar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
16
1
5
Order By: Relevance
“…In both studies, one serious complication occurred, namely a tongue base infection. N evertheless, in a larger series we could demonstrate that antibiotic prophylaxis reduces the number of side-effects; further tongue base infections have not been recorded (24). In the present study and in the larger series cited above we never observed any relevant postoperative complications due to deterioration of OSAS induced by tissue edema.…”
Section: Postoperative Morbidity and Complicationscontrasting
confidence: 45%
See 2 more Smart Citations
“…In both studies, one serious complication occurred, namely a tongue base infection. N evertheless, in a larger series we could demonstrate that antibiotic prophylaxis reduces the number of side-effects; further tongue base infections have not been recorded (24). In the present study and in the larger series cited above we never observed any relevant postoperative complications due to deterioration of OSAS induced by tissue edema.…”
Section: Postoperative Morbidity and Complicationscontrasting
confidence: 45%
“…In a previous study we have demonstrated that the application of higher amounts of energy does not lead to relevant increases in postoperative morbidity or in the number of complications observed (24).…”
Section: Postoperative Morbidity and Complicationsmentioning
confidence: 91%
See 1 more Smart Citation
“…The survey was modified from other surveys used in the literature to determine knowledge or impressions of SLPs on feeding tube placement [34], written language [35] and nonspeech oral motor exercises [26]. This survey was developed using questions focused on four primary areas: personal demographics, work experience, extent of knowledge of the obese swallow and impressions of the obese swallow.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Although there are different surgical techniques for treatment of OSAS (e.g. uvulopalatopharyngoplasty), existing research has not objectively addressed differences in swallowing, speech or taste pre-surgery and postsurgery but instead has used subjective means of determining differences [25][26][27][28]. More research is needed to compare the swallow (and speech) of persons who are obese and present with OSAS and their typical-weight counterparts to determine if objective differences exist.…”
Section: Introductionmentioning
confidence: 99%